Kajian Yuridis Penyelesaian Wanprestasi Pada Bank Perkreditan Rakyat dengan Skema Kredit Linkage - Elfarinda, Laila; Mochtar, Dewi Astutty; Wisnuwardhani, Diah Aju (Postgraduate University of Merdeka Malang, 2024)
In the Linkage product, banks provide facilities for BPR (Rural Banks) to obtain credit facilities of significant amounts to ensure smooth operations and productive capital for debtors in need. Additionally, the guarantees used are in the form of Asset Replacement or Nominative Performing Loans. The list of Nominative Performing Loans provided by BPR includes the names of borrowing debtors, personal data of the BPR debtors, including identification numbers, addresses, telephone numbers, account numbers at the BPR, and the credit limits utilized. This creates legal issues in the event of default regarding loans that are not secured by valuable assets. This research is conducted using a normative legal approach, where the author will delve into positive legal norms and other legal literature. The research questions raised are: What is the process of credit agreements under the Linkage scheme with Asset Replacement or Nominative Performing Loan collateral and how is the resolution process for defaulting debtors under the Linkage scheme with Asset Replacement or Nominative Performing Loan collateral. The research findings indicate that the credit agreement process under the Linkage scheme with Asset Replacement or Nominative Performing Loan collateral is valid in contractual law, as it meets the validity requirements stipulated in Article 1320 of the Civil Code. Furthermore, the resolution process is carried out through judicial procedures, namely by filing a default lawsuit accompanied by a request for asset seizure against the debtor's property, as regulated in Article 1131 of the Civil Code.